Stressful life events are associated with the diagnosis of systemic autoimmune rheumatic diseases among adults - Bauer Ventura, Iazsmin; Goldberg, Maya E; Schiffenbauer, Adam; Shi, Min; Volochayev, Rita; Jackson, Sharon H; Jansen, Anna; Bayat, Nastaran; Noroozi Farhadi, Payam; Parks, Christine G; Weinberg, Clarice R; Picardi, Angelo; et al. (Clinical and experimental rheumatology, 2025)
To assess the association between life events and subsequent diagnosis of systemic autoimmune rheumatic diseases (SARDs) by comparing siblings discordant for SARDs and unrelated controls. Life events 12 months prior to SARD diagnosis/reference date were queried using the Interview for Recent Life Events in 227 adults (96 probands with SARDs, 78 siblings, 53 controls). Probands were matched by age, sex, and race with their unaffected siblings or with unrelated controls. Logistic regression was used to calculate the relative odds of SARDs in relation to life events scores, adjusting for age, sex, race/ethnicity, education, and ever smoking. The study identified consistent trends of probands reporting greater numbers of total and highly stressful events, and higher stress ratings than their unaffected siblings. Probands reported greater numbers and higher stress ratings of total, uncontrollable, and undesirable events compared to unrelated controls (p<0.001-0.024). The number of highly stressful events and the scores of weighted major events were also greater in probands and siblings compared to unrelated controls (p<0.001-0.046). The number of total, major, uncontrollable, undesirable, and highly stressful life events (OR range 1.31-1.64, p-value range 0.001-0.049), along with their corresponding stress ratings (OR range 1.22-1.51, p-value range <0.001-0.016), were associated with higher odds of SARD diagnosis, based on probands compared to controls. This case-control study of life events preceding SARDs diagnosis using a validated life events questionnaire provides support for an aetiologic role of negative life events and psychological stress in SARDs among adults.